Frequencies of HLA-DQ2 and HLA-DQ8 haplotypes in Czech and Slovak coeliac patients and the healthy population - Wroblova, Katerina; Kolorz, Michal; Pav, Igor; Horakova, Zuzana; Filipova, Petra; Bartos, Milan; Bartosova, Ladislava (Acta Biochimica Polonica, 2014)
Coeliac disease is an autoimmune disorder with genetic predisposition. The aim was to determine the frequency of HLA-DQ2 and HLA-DQ8 in Czech and Slovak patients and the healthy population. The study included 127 patients and 66 healthy volunteers. HLA-DQ2 was identified in 85.03% patients, and 24.24% healthy individuals (P=0.0001; OR17.7632; CI=8.4347-37.4088). HLA-DQ8 was identified in 11.81% patients and 15.5% healthy individuals. HLA-DQ8 occurred more often in HLA-DQ2-negative patients compared to HLA-DQ2-positive patients (P=0.0494; OR3.5; CI 1.0428-11.7468). At least one of the studied HLA-variants was found more often in patients than in healthy individuals (P=0.0001; OR58.8; CI 7.6856-449.8602).
Keywords: HLA-DQ antigeny; Ethnicity; Genetic Association Studies; Slovakia; Gene Frequency; frekvence genu; Slovenská republika; Česká republika; Celiac Disease; etnicita; genetické asociační studie; HLA-DQ Antigens; celiakie; Czech Republic; Haplotypes; haplotypy; lidé; Humans; genetická predispozice k nemoci; Genetic Predisposition to Disease